Social Transformation in Urban Sufism: The Process of Selecting New and Popular (Rising Star) Scholars in Urban Environments - Mhd. Ade Putra Ritonga; Fadil Nurdin; Nunung Nurwati (Dinasti Publisher, 2024)
Social changes within Sufism occurring in urban environments have become an increasingly important topic in religious studies and current societal dynamics. This study explores the process of appointing new and prominent scholars (rising stars) in cities and their impact on the structure and development of Sufi communities. The research method used is library research, relying on data from various books and previous studies as primary sources, with a qualitative approach that includes in-depth interviews, active observation, and secondary data analysis. This study identifies key factors influencing the emergence of new scholars in urban environments, such as changes in spiritual preferences, the role of social media, and the impact of popular culture. The findings indicate that the selection of rising star scholars is driven by the urban community's need for a spiritual figure who can align Sufi teachings with the demands of modernity. Furthermore, the study reveals shifts in the power and spiritual authority structure within urban communities, where new scholars often leverage digital platforms to enhance their influence. The influence of contemporary scholars on urban societal transformation in the context of urban Sufism has two sides. On one hand, they can bring positive innovation and social engagement. On the other hand, potential fragmentation, commercialization, and conflict with tradition also need to be considered. This research provides insights into how the Sufi tradition adapts in urban contexts and the development of spiritual leadership.